Singularities Produced by the Reflection and Interaction of Two Progressing Waves (Journal of Partial Differential Equations, 1990)
We give an example to show that there will be anomalous singularities on the forward half light cone issuing from the reflection point after the reflection at the boundary of two progressing waves carrying singularities. It perfects the results of [1].